2016
DOI: 10.1111/aos.13316
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity in relation to development and progression of myopia – a systematic review

Abstract: On a global scale, myopia is one of the most common causes of visual impairment. Given the increasing prevalence of myopia, it is vital to understand the pathogenesis and to identify potential interventions. Some studies have described physical activity as a potential correlation for myopia. The objective of this study was to make a systematic review regarding the correlation between physical activity and myopia. A total of 263 papers were identified in a systematic database search of PubMed/Medline and Embase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
60
2
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(70 citation statements)
references
References 31 publications
5
60
2
3
Order By: Relevance
“…Our findings corresponded with previous studies, although there are some conflicting results in the literature (Suhr Thykjær et al. ). The protective role of lifestyle choices, such as PA and time outdoors, has been an area of interest in the last 10 years (Jacobsen et al.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Our findings corresponded with previous studies, although there are some conflicting results in the literature (Suhr Thykjær et al. ). The protective role of lifestyle choices, such as PA and time outdoors, has been an area of interest in the last 10 years (Jacobsen et al.…”
Section: Discussionsupporting
confidence: 92%
“…In a systematic review investigating PA and myopia, Suhr Thykjær et al. () found a consistent relationship between more PA and less myopia. They concluded that there was no evidence for an independent effect of PA.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…; Suhr Thykjaer et al. ). Theories of the underlying physiological mechanisms include impact on the emmetropization due to changes in choroidal blood flow (Nickla & Wallman ; Summers ) and light‐sensitive dopamine levels (McCarthy et al.…”
Section: Introductionmentioning
confidence: 99%